2022
DOI: 10.1007/s12369-022-00875-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Humans in Surgery Automation

Abstract: Innovation in healthcare promises unparalleled potential in optimizing the production, distribution, and use of the health workforce and infrastructure, allocating system resources more efficiently, and streamline care pathways and supply chains. A recent innovation contributing to this is robot-assisted surgeries (RAS). RAS causes less damage to the patient's body, less pain and discomfort, shorter hospital stays, quicker recovery times, smaller scars, and less risk of complications. However, introducing a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These factors pose a challenge to the innovation management, especially as the division of autonomy in technologyenabled healthcare delivery is shifting rapidly. Early examples of this can be found in robot-assisted surgery (RAS), where increasing levels of autonomy complicate the scene [93]. The same can be said for healthcare delivery through telehealth devices and applications, where liability attribution for the risks arising from the interplay between stakeholders remains unclear, and legal frameworks to address this issue comprehensively are currently lacking.…”
Section: Other Considerationsmentioning
confidence: 99%
“…These factors pose a challenge to the innovation management, especially as the division of autonomy in technologyenabled healthcare delivery is shifting rapidly. Early examples of this can be found in robot-assisted surgery (RAS), where increasing levels of autonomy complicate the scene [93]. The same can be said for healthcare delivery through telehealth devices and applications, where liability attribution for the risks arising from the interplay between stakeholders remains unclear, and legal frameworks to address this issue comprehensively are currently lacking.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Healthcare institutions and regulatory bodies must work together to establish clear guidelines and frameworks for defining liability, particularly in cases where autonomous AI plays a significant role in surgical decision-making and execution. Addressing these legal complexities is essential to safeguarding both patient rights and the interests of healthcare professionals [69].…”
Section: Ethical and Legal Challengesmentioning
confidence: 99%
“…We are now on the verge of realizing this vision in our daily work. For instance, in surgical settings, a collaborative triad emerges among human surgeons, dedicated support staff, and autonomous robotic systems, illustrating a dynamic partnership that allocates responsibilities across a spectrum of intricate tasks and meticulous oversight [6]. Research has shown that HATs can be more effective in task completion and can have slightly better team satisfaction than all-human teams [7].…”
Section: Introductionmentioning
confidence: 99%